ANALISIS PENDAPATAN KERIPIK SUKUN PADA INDUSTRI RUMAH TANGGA âCITRA LESTARI PRODUCTIONâ DI KOTA PALU SULAWESI TENGAH - Made Antara, Samsiarti (AGROTEKBIS, 2016)
Sukun is one of the agricultural commodities that is able to fullfil human necessity in daily life and is considered to have promising market opportunities and prospects. Central Sulawesi possesses a sufficient land of Sukun tree spreading. Sukun now can be processed to made chips, it is able to give benefits to industry. This research aims to determine the revenue earned for the domestic industry,